Ukronier i Svend Åge Madsens forfatterskab - Kraglund, Rikke Andersen (K&K - Kultur og Klasse, 2011)
NON-MIMETIC SCENARIOS IN SVEND AAGE MADSEN’S WRITINGS | In 2010 the article “Unnatural Narratives, Unnatural Narratology: Beyond Mimetic Models” appeared in the American journal Narrative, where the theory of an ‘unnatural narratology’ was presented. This theory opposes the claim that the basic elements of narrative can be explained by models based on real-world parameters. According to this theory, narratives that feature impossible or anti-mimetic elements have been marginalized in existing narratological frameworks. This article discusses some of the concepts that are developed in the first manifesto of unnatural narratology and illustrates the applicability of these concepts in relation to a small selection of the numerous non-mimetic scenarios found in Svend Aage Madsen’s works.